Reviewing the recording quality of a local string instrument (Sape) from the perspective of sound preservation - Musib Ahmad Faudzi, (Universiti Pendidikan Sultan Idris, 2016)
Reviewing the recording quality of a local string instrument (Sape) from the perspective of sound preservation by Musib Ahmad Faudzi,